Emerging nanosonosensitizers augment sonodynamic-mediated antimicrobial therapies - Qinglin Xu; Weijun Xiu; Qiang Li; Yu Zhang; Xiaoye Li; Meng Ding; Dongliang Yang; Yongbin Mou; Heng Dong (Materials Today Bio, 2023)
With the widespread prevalence of drug-resistant pathogens, traditional antibiotics have limited effectiveness and do not yield the desired outcomes. Recently, alternative antibacterial therapies based on ultrasound (US) have been explored to overcome the crisis of bacterial pathogens. Antimicrobial sonodynamic therapy (aSDT) offers an excellent solution that relies on US irradiation to produce reactive oxygen species (ROS) and achieve antibiotic-free mediated antimicrobial effects. In addition, aSDT possesses the advantage of superior tissue penetrability of US compared to light irradiation, demonstrating great feasibility in treating deep infections. Although existing conventional sonosensitizers can produce ROS for antimicrobial activity, some limitations, such as low penetration rate, nonspecific distribution and poor ROS production under hypoxic conditions, result in suboptimal sterilization in aSDT. Recently, emerging nanosonosensitizers have enormous advantages as high-performance agents in aSDT, which overcome the deficiencies of conventional sonosensitizers as described above. Thus, nanosonosensitizer-mediated aSDT has a bright future for the management of bacterial infections. This review classifies the current available nanosonosensitizers and provides an overview of the mechanisms, biomedical applications, recent advances and perspectives of aSDT.